Gendered differences in perceived employability among higher education students in STEM and non-STEM disciplines. (3rd July 2021) - Bennett, Dawn; Bawa, Sherry; Ananthram, Subramaniam
ABSTRACT: Numerous policy interventions promote gender equity within STEM (Science, Technology, Engineering and Mathematics) higher education enrolments and careers. Despite this, women in many countries continue to be under-represented and encounter barriers to access and career progression. These concerns are often attributed to gendered technical/technological confidence and gendered perceptions of career. Using an online self-assessment tool, this study reports the employability confidence of 12, 708 university students. Utilising five employability constructs to assess the confidence of STEM and non-STEM women and men, we found that women in STEM were often more confident than men. Moreover, women in STEM reported higher confidence than women in non-STEM. These novel findings might help inform policies and strategies to attract and retain women in STEM degrees and careers. We emphasise the need to focus on career transition and advancement support given that women are confident whilst studying, yet less likely than men to advance in their careers.